Input and output in distributive theory. - Eyal, Nir; Herlitz, Anders (Nous (0029-4624), 2023)
Distributive theories evaluate distributions of goods based on candidate recipients' characteristics, e.g. how well off candidates are, how deserving they are, and whether they fare below sufficiency. But such characteristics vary across possible worlds, so distributive theories may differ in terms of the world which for them settles candidates' characteristics. This paper examines how distributive theories differ in terms of whether candidate recipients' relevant characteristics are grounded in the possible world that would take place if the distributor does not intervene (call it the "input" world) or if they are grounded in each possible world that the distributor can bring about through different decisions (call each an "output" world). We illustrate the importance of this distinction in relation to one distributive theory, prioritarianism. As we show, both input and output versions of prioritarianism are plausible interpretations of the literature, and there are good reasons to take input prioritarianism seriously. Ultimately, however, we argue that input prioritarianism should be rejected.